What helps young people in Australia create healthy relationships after growing up in domestic violence? - Buchanan, Fiona (Journal of family violence, 2025)
Purpose: This study aimed to discover what enables young people in Australia to create healthy relationships despite exposure to domestic violence (DV) in their families of origin during their formative years. Method: Taking an ecological systems theory and mixed qualitative methods approach, a survey was designed to identify different factors that young people recalled as helpful when they were enduring DV as children and, later, as young adults. Two hundred and three young people aged 18-30 years completed the national online survey. In addition, to achieve richer insights and an understanding of the complexities in individual experiences, fourteen of the survey respondents then participated in in-depth life-history interviews. Results: Although most participants believed they had been adversely affected by growing up in DV, empathetic family members and friends, achievements through school and sports, and gaining knowledge about DV and healthy relationships, often through social media, enabled many to distinguish the difference between healthy relationships and DV. These influences then affected how they approached partnership relationships as they matured. Conclusion: Analysis of survey and interview data led us to consider that all strata of the ecosystem could, through applying prevention and early intervention strategies, support children and young people to identify and choose healthy relationships rather than accept prescriptive, pathologizing predictions for their future.